Molecular photoprotection of human keratinocytes in vitro by the naturally occurring mycosporine‐like amino acid palythine. (25th March 2018) - Lawrence, K.P.; Gacesa, R.; Long, P.F.; Young, A.R.
Summary: Background: Solar ultraviolet radiation (UVR) induces molecular and genetic changes in the skin, which result in skin cancer, photoageing and photosensitivity disorders. The use of sunscreens is advocated to prevent such photodamage; however, most formulations contain organic and inorganic UVR filters that are nonbiodegradable and can damage fragile marine ecosystems. Mycosporine‐like amino acids (MAAs) are natural UVR‐absorbing compounds that have evolved in marine species for protection against chronic UVR exposure in shallow‐water habitats. Objectives: To determine if palythine, a photostable model MAA, could offer protection against a range of UVR‐induced damage biomarkers that are important in skin cancer and photoageing. Methods: HaCaT human keratinocytes were used to assess the photoprotective potential of palythine using a number of end points including cell viability, DNA damage (nonspecific, cyclobutane pyrimidine dimers and oxidatively generated damage), gene expression changes (linked to inflammation, photoageing and oxidative stress) and oxidative stress. The antioxidant mechanism was investigated using chemical quenching and Nrf2 pathway activation assays. Results: Palythine offered statistically significant protection ( P < 0·005) against all end points tested even at extremely low concentrations (0·3% w/v). Additionally, palythine was found to be a potent antioxidant, reducing oxidatively generated stress, even when added after exposure. Conclusions: Palythine is an extremely effective multifunctional photoprotective molecule in vitro that has potential to be developed as a natural and biocompatible alternative to currently approved UVR filters. Abstract : What's already known about this topic? Mycosporine‐like amino acids (MAAs) are photoprotective molecules found in marine organisms but there are few data on their ability to protect skin cells from the adverse effects of solar ultraviolet radiation (UVR). The European Chemicals Agency (ECHA) is concerned about the potential adverse health and ecotoxic effects of eight of 16 commonly used sunscreen filters in Europe. The Environmental Effects Assessment Panel (EEAP) of the United Nations Environment Programme has expressed similar concerns. What does this study add? Palythine, an MAA extracted from an edible seaweed, affords photoprotection against a wide range of adverse effects in HaCaT keratinocytes exposed to solar simulating and ultraviolet A radiation. Of note is protection against two types of DNA photolesions; cyclobutane pyrimidine dimers and 8‐oxo‐7, 8‐dihydroguanine. Palythine is also a potent antioxidant that offers protection even when added after UVR exposure. What is the translational message? MAAs should be considered for development as natural biocompatible sunscreens that may address the concerns of the ECHA and EEAP. Linked Comment: Cooke. Br J Dermatol 2018; 178 :1239–1240 . Respond to this article